Chronic Lymphocytic Leukemia: A Literature Review - Maulana, Muhammad Rafi; Nurmawaddah, Intan; Ilmiah, Janiya Abdila; Damayanti, Ida Ayu Andara; Wiguna, I Made Danuarta; Anggoro, Joko; Maulana, Akhada (Jurnal Biologi Tropis, 2025)
Chronic Lymphocytic Leukemia (CLL) is a slowly progressing hematological cancer characterized by the accumulation of abnormal B lymphocytes in the blood, bone marrow, and lymphatic tissue, commonly affecting the elderly. This review aims to comprehensively review the epidemiology, molecular basis of the disease, clinical symptoms, diagnosis, and therapeutic advances of CLL, emphasizing the importance of shifting treatment approaches towards more precision therapy. A literature search was conducted through PubMed, Scopus, and Web of Science using the keywords "Chronic Lymphocytic Leukemia", "epidemiology", "molecular basis of the disease", and "targeted therapy", with publication criteria between 2018–2025, full text, and topic relevance. Analysis was conducted using a narrative review and thematic synthesis approach to identify epidemiological trends, therapeutic effectiveness, and clinical implications. The results showed that the incidence of CLL is higher in Western countries compared to Asia, with a higher prevalence in elderly men. The main genetic factors that play a role include del(13q), del(17p), and TP53 mutations. Over the past decade, targeted therapies such as second-generation Bruton's tyrosine kinase inhibitors (acalabrutinib, zanubrutinib) and the venetoclax-obinutuzumab combination have been shown to improve remission rates with fewer side effects compared to chemoimmunotherapy. Minimal Residual Disease (MRD) status has become an important marker for determining when therapy can be stopped early. In conclusion, this review underscores the crucial role of biomarkers and MRD in modern CLL management. Future developments include the integration of personalized therapy approaches and translational research to develop more effective and safe treatment strategies.